INTEGRATION OF Fe IN NATURAL AND SYNTHETIC Al-PYROPHYLLITES: AN INFRARED SPECTROSCOPIC STUDY - Lantenois S.; Beny J.M.; Muller F.; Champallier R. (My University, 2007)
Numerous studies focus on the relationships between chemical composition and OH-band positions in the infrared (IR) spectra of micaceous minerals. These studies are based on the coexistence, in dioctahedral micas or smectites, of several cationic pairs around the hydroxyl group which each produce a characteristic band in the IR spectrum. The aim of this work is to obtain the wavenumber values of the IR OH vibration bands of the (Al-Fe3+)-OH and (Fe3+- Fe3+)-OH local cationic environments of 'pyrophyllite type' in order to prove, disprove or modify a model of dioctahedral phyllosilicate OH-stretching band decomposition. Natural samples are characterized by powder X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Raman spectroscopies and electron microprobe; the hydrothermal synthesis products are also analysed by powder XRD and FTIR after inductively coupled plasma measurements to obtain the chemical compositions of starting gel phases. Natural samples contain some impurities which were eliminated after acid treatment; nevertheless, a small Fe content is found in the pyrophyllite structure. The amount of Fe which is incorporated within the pyrophyllite structure is much more important for the synthetic samples than for the natural ones. The IR OH bands were clearly observed in both natural and synthetic pyrophyllites and assigned to hydroxides bonded to (Al-Al), (Al-Fe) and (Fe-Fe) cationic pairs. During this study, three samples were analysed by DTG to check the cis- or trans-vacant character of the layers and to determine the influence of this structural character on the OH-stretching band position in IR spectroscopy. © 2007 The Mineralogical Society.
Keywords: CIS-TRANS-VACANT; Fe DEFAULTS; FTIR SPECTROSCOPY; HYDROTHERMAL SYNTHESES; PYROPHYLLITE